Learning Disabilities and Academic Achievement amongst School Children in Accra. - Attah, D.A. (University of Ghana, 2010)
Learning disabilities (LD) may be one of the most common and serious pervasive childhood disabilities, with prevalence estimates between 2% and 10%. Yet, stakeholders, parents, teachers and die society at large know little concerning the effect of learning disabilities on school children in Ghana. The current study sought to bridge this gap by examining the impact of learning disabilities on academic achievement among school children in Accra. The study comprised of three groups; children with learning disabilities, children without learning disabilities and children with other neurological disorders. A total of 131 children were compared on measures of academic achievement, adaptive behaviour, problem behaviour, nonverbal intelligence and a cognitive flexibility Test. The results revealed significant groups differences. Specifically, children with learning disabilities scored lower on measures of academic achievement and non-verbal intelligence compared to children without learning disabilities, but higher than children with other neurological disorders. Other findings showed that the performance of children with learning disabilities was impaired on the part B of the cognitive flexibility Test but not on the part A. Further, children with learning disabilities as well as children with other neurological disorders showed evidence of lower social skills. Contrary to expectations, few significant differences were found between children with learning disabilities and children without learning disabilities on measures of problem behaviour. Implications for future research and for practice are discussed.
Thesis(M.Phil)- University of Ghana,2010